FACTORS THAT INFLUENCE CONSUMER DECISION MAKING IN TERESINENSE: AN ANALYSIS OF BEHAVIOR WHEN PURCHASING CARS (REMUNOM, 2025)
Decision-making to make a purchase has always been a widely studied topic in scenarios of great competition and competitiveness as we currently experience. The present work aims to analyze the aspects that influence consumers in Teresina in the decision-making process to purchase motor vehicles. Using a quantitative approach, the research was carried out using a questionnaire with 151 respondents, providing a detailed view of the internal and external factors that affect this decision. The results show that internal factors such as gender, age group, marital status, average family income, education level and occupation are significant determinants in the purchasing decision. The main reasons for purchasing are related to family and professional needs, with financing being the main form of acquisition. This study is related to Ajzen's Theory of Planned Behavior (1991), which suggests that attitudes, subjective norms and perceived control are important determining factors in consumers' purchasing intentions and actual behavior. Research has shown that purchase intention is shaped by attitudes and perceptions of control. Furthermore, the research is related to Maslow's Theory of Human Needs (1943), which postulates that human needs are hierarchical in a pyramid, from basic to self-realization. In the context of this study, the needs for security, social status and self-fulfillment were identified as significant motivations for purchasing vehicles. Owning a vehicle meets both basic mobility needs and psychological needs for status and self-actualization.